Contributions to the study of contemporary racism in Portugal (Cadernos de Sociomuseologia, 2025)
This article proposes a reflection on the origins of contemporary racism, insofar as it is a consequence of the social structure in which we live (no one is born racist). Indeed, it is our understanding that the justification for contemporary racism is constituted within the framework of colonization in Africa from the end of the 19th century, without forgetting that the previous period of the slave-owning process certainly left a legacy of exclusion and suffering for enslaved people. This article aims to identify elements that can contribute to understanding the origins of contemporary racism in Portugal, particularly against Black people. Indeed, we believe it is important to distinguish, in the history of racism in Portuguese society, the various periods and their own characteristics. The forms that racism took during the slave-owning period, as well as the justifications underlying its existence, differ from those that characterize the occupation of African territory in the wake of the Berlin Conference of 1884-85.Keywords: Racism, origins of racism, Colonial War, Colonial museums, Perverse memory